2016
DOI: 10.1039/c5cs00769k
|View full text |Cite
|
Sign up to set email alerts
|

Inorganic perovskite photocatalysts for solar energy utilization

Abstract: The development and utilization of solar energy in environmental remediation and water splitting is being intensively studied worldwide. During the past few decades, tremendous efforts have been devoted to developing non-toxic, low-cost, efficient and stable photocatalysts for water splitting and environmental remediation. To date, several hundreds of photocatalysts mainly based on metal oxides, sulfides and (oxy)nitrides with different structures and compositions have been reported. Among them, perovskite oxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
234
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 471 publications
(235 citation statements)
references
References 432 publications
(486 reference statements)
0
234
0
1
Order By: Relevance
“…Recently, perovskite‐type metal oxides, such as SrTiO 3 and NaTaO 3 , have attracted widespread attention in the fields of photocatalytic water splitting and degradation of organic pollutants in virtue of their stable layered structure, effectiveness in charge separation, high corrosion resistance, outstanding physical and chemical properties, and excellent photocatalytic activity . Among these perovskite materials, sodium niobate (NaNbO 3 ) has emerged as a potential candidate for photocatalysis and is touted as an environmentally friendly and viable replacement of widely used TiO 2 . Gu et al reported that the cubic NaNbO 3 nanowires with 0.5 wt% of Pt cocatalyst could split water to H 2 with quite high efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, perovskite‐type metal oxides, such as SrTiO 3 and NaTaO 3 , have attracted widespread attention in the fields of photocatalytic water splitting and degradation of organic pollutants in virtue of their stable layered structure, effectiveness in charge separation, high corrosion resistance, outstanding physical and chemical properties, and excellent photocatalytic activity . Among these perovskite materials, sodium niobate (NaNbO 3 ) has emerged as a potential candidate for photocatalysis and is touted as an environmentally friendly and viable replacement of widely used TiO 2 . Gu et al reported that the cubic NaNbO 3 nanowires with 0.5 wt% of Pt cocatalyst could split water to H 2 with quite high efficiency.…”
Section: Introductionmentioning
confidence: 99%
“…[30][31][32][33][34] In the crystal structure of ideal perovskite, the Ac ation is 12-fold coordinated and the Bc ation is 6fold coordinated to the oxygen anions. [30][31][32][33][34] In the crystal structure of ideal perovskite, the Ac ation is 12-fold coordinated and the Bc ation is 6fold coordinated to the oxygen anions.…”
Section: Introductionmentioning
confidence: 99%
“…Compared to the rapid development of complex metal oxide photocatalysts [5,12], making a simple binary photocatalyst TiO 2 active to fully harvest visible light is a challenge [13][14][15][16][17][18][19][20][21][22]. TiO 2 is easily available and low-cost, but has no visible light absorption due to its large bandgap of about 3 eV.…”
Section: Introductionmentioning
confidence: 99%